Macrophage regulation of angiogenesis in health and disease. (November 2021) - Martin, Paul; Gurevich, David Baruch
Abstract: Macrophages are primarily known as phagocytic innate immune cells, but are, in fact, highly dynamic multi-taskers that interact with many different tissue types and have regulatory roles in development, homeostasis, tissue repair, and disease. In all of these scenarios angiogenesis is pivotal and macrophages appear to play a key role in guiding both blood vessel sprouting and remodelling wherever that occurs. Recent studies have explored these processes in a diverse range of models utilising the complementary strengths of rodent, fish and tissue culture studies to unravel the mechanisms underlying these interactions and regulatory functions. Here we discuss how macrophages regulate angiogenesis and its resolution as embryonic tissues grow, as well as their parallel and different functions in repairing wounds and in pathologies, with a focus on chronic wounds and cancer.